Recent advances in robot‐assisted echography: combining perception, control and cognition. Issue 3 (8th September 2020) - Lu, Zhenyu; Li, Miao; Annamalai, Andy; Yang, Chenguang
Abstract : Echography imaging is an important technique frequently used in medical diagnostics due to low‐cost, non‐ionising characteristics, and pragmatic convenience. Due to the shortage of skilful technicians and injuries of physicians sustained from diagnosing several patients, robot‐assisted echography (RAE) system is gaining great attention in recent decades. A thorough study of the recent research advances in the field of perception, control and cognition techniques used in RAE systems is presented in this study. This survey introduces the representative system structure, applications and projects, and products. Challenges and key technological issues faced by the traditional RAE system and how the current artificial intelligence and cobots attempt to overcome these issues are summarised. Furthermore, significant future research directions in this field have been identified by this study as cognitive computing, operational skills transfer, and commercially feasible system design.